A Cultural Biography of rural tourist towns (Huellas, 2021)
Since the crisis with the agriculture and livestock sector, which took place in the late 1990s and early 2000s, various state and non-state actors have tried to stimulate, socially and economically, rural towns in Argentina. In this context, tourism is becoming increasingly frequent in initiatives and programs as a revitalization strategy, considering its positive aspects. However, the tourism development process entails a number of material and symbolic transformations that can provoke tensions. Hence, in this article we propose to critically analyze how these processes are generated through the construction of a “cultural biography”. This proposal allows us to investigate and contextualize the implications of tourism in rural towns.
Keywords: rural towns; tourism; revitalization strategies; tensions